The structure of poetic discourse in the poems of Da'bil Al-Khuza'i (rhythm – meaning) (Journal of the College of Basic Education, 2024)
The text is formed with harmonious parts that illustrate one unit that complete each other. The rhythm calls for the meaning, and the meaning necessarily brings the purpose and the poetic features. The poetic images are in harmony with the rhythm in a direct manner. The structural studies of the poetic and critical discourse has confirmed the structure and harmony of the its parts. As long as the poetry of Al-tuffyat stems from the feeling, emotional decency and emotional experience, it came on as one temperament, as the emotional state of expression varies, from this point of view, the research seeks to highlight the aesthetic values in the tuffy poetic text in the poetry of Daabal Al-Khuzai, who writes about the imams (peace be upon them) and sang their courage, their exploits, and their emotional characteristics. Al-tuffyat of Daabal Al-Khuzai were the best representation of all this. The study was divided into two sections and preceded by an introduction and ended with a conclusion in which the researcher presented the most prominent findings of the research.